IOs Sensor Apps with Arduino / Allan, Alasdair - Allan, Alasdair
This book looks at how to integrate iOS devices into distributed sensors network, both to make use of its own on-board sensors in such networks, but also as a hub. "Learn how to connect the Arduino platform to any iOS device; build a simple application to control your Arduino directly from an iPad; gather measurements from an ultrasonic range finder and display them on your iPhone; connect an iPhone, iPad, or iPod Touch to an XBee radio network; explore other methods for connecting external sensors to iOS, including Ethernet and the MIDI protocol"--Provided by publisher.